Experimental study on repair of fatigue cracks at welded web gusset joint using CFRP strips - Nakamura, Hitoshi; Jiang, Wei; Suzuki, Hiroyuki; Maeda, Ken-ichi; Irube, Takao (Thin-walled structures, 2009)
This paper presents repair methods of fatigue cracks using CFRP strips. In particular, the subject of repair is fatigue cracks initiated at welded web gusset joints, which are the typical details in steel bridges. Several repair methods were investigated experimentally focusing on weld details. In addition, more effective repair methods were also investigated using combination of CFRP strips and drill-holes. As a result, it was found that fatigue life after repair was significantly improved. Therefore, the authors confirmed the feasibility of the proposed technique as a useful repair method to improve fatigue life of steel structures.